2013
DOI: 10.1002/pola.26711
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐mediated controlled radical polymerization in continuous flow processes: Synergy between polymer reaction engineering and innovative chemistry

Abstract: Copper(0)-mediated controlled radical polymerization (CRP), or single-electron transfer-living radical polymerization (SET-LRP) is a robust and dynamic technique that has attracted considerable academic and industrial interest as a synthetic tool for novel value-added materials. Although SET-LRP possesses many advantages over other forms of CRP, this novel chemistry still requires concurrent engineering solutions for successful commercial application. In this highlight, the evolution of atom-transfer radical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
93
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(93 citation statements)
references
References 144 publications
(263 reference statements)
0
93
0
Order By: Relevance
“…9 In ATRP, the use of low oxidation state transition-metal catalyst (commonly Cu I salt) inevitably leads to contamination of products and time-consuming deoxygenation process. [9][10][11] Scientists have been focusing on diminishing the catalyst dosage and applying high oxidation state catalytic complex or metallic copper through experimental and kinetic modeling investigations. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] For example, initiators for continuous activator regeneration (ICAR) ATRP, [13][14][15][16] activators regenerated by electron transfer (ARGET) ATRP, [17][18][19] single electron transferliving radical polymerization (SET-LRP), [20][21][22] supplemental activator and reducing agent (SARA) ATRP, [23][24][25] and electrochemically mediated ATRP (eATRP) 26 have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…9 In ATRP, the use of low oxidation state transition-metal catalyst (commonly Cu I salt) inevitably leads to contamination of products and time-consuming deoxygenation process. [9][10][11] Scientists have been focusing on diminishing the catalyst dosage and applying high oxidation state catalytic complex or metallic copper through experimental and kinetic modeling investigations. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] For example, initiators for continuous activator regeneration (ICAR) ATRP, [13][14][15][16] activators regenerated by electron transfer (ARGET) ATRP, [17][18][19] single electron transferliving radical polymerization (SET-LRP), [20][21][22] supplemental activator and reducing agent (SARA) ATRP, [23][24][25] and electrochemically mediated ATRP (eATRP) 26 have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…6,7,[48][49][50][51]57,[71][72][73][74][75][76][77] Narrow molecular weight distribution is an important feature of the polymers prepared by LRP but the most significant structural parameter of these polymers is the quantitative or near quantitative chain-end functionality combined with narrow molecular weight distribution. Chain-end functionality is the major parameter of a polymer that allows the construction of complex architectures such as multiple block copolymers, 64,73,[76][77][78][79] and dendrimers by iterative synthesis. [77][78][79][80][81] In a previous publication from our laboratory it was reported that the Cu(0) mediated SET-LRP of 2-hydroxyethyl acrylate (HEA) in H 2 O and in mixtures of protic solvents with H 2 O produces a gel of poly(HEA) (PHEA) exclusively on the surface of the catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…10,46,57 The catalyst most frequently employed in SET-LRP is Cu(0) in the form of powder 2,4,12,58 including powder generated by the disproportionation of Cu(I)X in a large diversity of solvents, 12 wire, 12,64,69 activated wire [59][60][61][62] and tubes. 63,64 Almost all initiators employed in other metal catalyzed LRP such as alkyl halides, 65,66 sulfonyl halides, 33,48,65,[67][68][69] N-halides 2,70 can be used as such or modified to become soluble for SET-LRP in various media including H 2 O. Only very few systematic investigations on SET-LRP with Cu(0) generated by disproportionation of Cu(I)X "in situ" in water 26,37,38,42 and in mixtures of water with other solvents are available.…”
Section: Introductionmentioning
confidence: 99%
“…Much work in SRP research makes use of controlled radical and other living type reactions [9][10][11][12][13][14] nucleobase polymers [15,16], and information containing polymers [17,18].…”
Section: Background and Motivationmentioning
confidence: 99%